The relationship between serum cytokine profile and vitamin D in calves with neonatal diarrhea - Caliskan, Mehmet; Dabak, Murat; Tumer, Kenan Cagri (Academic Press Ltd- Elsevier Science Ltd, 2023)
It is important to know the characteristics of the immunological response in newborn calf diarrhea, which is often caused by bacterial, viral and protozoal pathogens. Cytokines are proteins that serve as chemical mes-sengers to regulate the innate and adaptive arms of the immune response. Changes in circulatory cytokine levels provide valuable information for understanding the pathophysiological process and monitoring disease pro-gression and inflammation. Vitamin D has important immunomodulatory effects, which include enhancing the innate immune system and inhibiting adaptative immune responses. The objective of this study was to evaluate the relationship between serum cytokine profile and vitamin D level in neonatal calves with diarrhea. The study population was comprised of 40 neonatal calves, 32 of which had diarrhea and 8 of which were healthy calves. The calves with diarrhea were allocated to four groups according to bacterial (Escherichia coli), viral (Rotavirus, Coronavirus) and protozoal (Cryptosporidium parvum) etiologies. Circulatory vitamin D metabolites (25-hydrox-yvitamin D, 1,25-dihydroxyvitamin D) and cytokines (TNF-alpha, IFN-gamma, IL-1 beta, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13 and IL-17) in the calves were determined. There was no statistically significant difference among the groups in 25-hydroxyvitamin D levels. 1,25-dihydroxyvitamin D levels were higher in Coronavirus and E. coli groups compared to the controls. Serum levels of all cytokines except for IL-13, were higher in E. coli group than those of the control group. As a result, differences in serum cytokines and vitamin D levels according to etiological factors in calf diarrhea indicate that vitamin D may play a role in the immune response in the disease.
Keywords: Neonatal Calf; Diarrhea; Cytokine; Vitamin D